Comparing the acute effects of active warm-up and stretching on parameters representing muscle tone, elasticity, and stiffness using MyotonPRO in male amateur competitive soccer players - Cai, Vincent Yingquan (2014)
This study investigated the effects of different warm-up and stretching protocols on the muscle parameters representing tone, elasticity and stiffness using the MyotonPRO device. Thirteen healthy and injury-free competitive soccer players underwent 4 treatment conditions (static/ dynamic stretching, active warm-up, control) in a randomized order on different days. Measurements of muscle parameters in the biceps and rectus femoris of both legs were taken before and after the treatment. Participants also underwent the Yo-yo Intermittent Recovery Test -Level 2 (IR2) to determine the effect of different treatments on intermittent high-intensity running performance. Paired t-tests were used to compare muscle parameters before and after treatment. Significant differences in elasticity were found after dynamic stretching [right biceps femoris, t (12) = 2.60, p = 0.02] and active warm-up [left rectus femoris, t (12) = 2.20, p = 0.048]. No significant differences in muscle parameters were observed after static stretching and control treatment. Repeated measures ANOVA did not find any significant differences in Yo-yo Intermittent Recovery Test performance after different treatments, F (1.98, 23.81) = 0.44, p = 0.65. MyotonPRO showed high reliability when operated by a novice user in field conditions (ICCs 0.73 – 0.87). Further analysis comparing typical error and smallest worthwhile change determined that MyotonPRO had marginal ability in detecting small worthwhile differences. The findings suggest that short durations of warm-up and stretching are not enough to elicit changes in muscle parameters. The ability of MyotonPRO in detecting small worthwhile changes should be further studied.